Analisis Kebutuhan Media Pembelajaran Games Box Berbasis STEM pada Materi Pencemaran Lingkungan SMA untuk Meningkatkan Kemampuan Berpikir Kreatif - Selvia Mariska Syahputri; Ida Sriyanti; Ismet (Jurnal Penelitian Pendidikan IPA, 2026)
This study explores students’ perceptions of creative thinking and examines the need to develop a STEM-based “Games Box” learning media for environmental pollution topics in high school physics. A descriptive quantitative approach was used, involving 277 students who completed a Likert-scale questionnaire covering six aspects, including creative thinking perception, learning media needs, STEM-based learning needs, interactive learning preferences, physical media accessibility, and readiness to use the Games Box. The findings show that students generally perceive their creative thinking abilities at a moderate level, particularly in fluency (mean = 2.87; 57.4%) and originality (mean = 2.74; 54.8%). At the same time, students express a clear need for more engaging and interactive learning media that integrate STEM approaches to help them understand abstract physics concepts more effectively. Responses also indicate a strong preference for learning media that are hands-on, game-based, and capable of making learning more meaningful and enjoyable. Overall, the results suggest that developing a STEM-based Games Box is both relevant and necessary to support creative thinking in learning environmental pollution. This study also emphasizes the importance of connecting environmental issues with physics concepts such as acoustics in noise pollution, thermodynamics in thermal pollution, and radiation in radioactive contamination. In general, the findings provide a solid foundation for designing innovative, student-centered learning media that align with the demands of 21st-century education.